Anaerobic digestion of waste activated sludge to produce volatile fatty acids and release nutrients using sodium citrate with sodium hydroxide pretreatment. Issue 1 (27th July 2022) - Zhou, Wuyang; Fang, Qian; Ding, Wenxue; Du, Zhili; Ren, Pengfei
Abstract: This study investigated the synergistic effect of sodium citrate (SC) and sodium hydroxide (NaOH) on the anaerobic digestion (AD) efficiency of waste activated sludge (WAS). Using the amount of SC as the control variable, changes in sludge cell cracking and AD performance under different pretreatment conditions was investigated. The optimum treatment conditions were a NaOH input of initial pH 10 and an SC concentration of 0.20 g/g total suspended solids. The pretreatment was monitored in 150 min. And the changes in soluble chemical oxygen demand (SCOD), soluble polysaccharide, soluble protein, volatile fatty acids (VFAs), PO4 3− ‐P and NH4 + ‐N during the pretreatment stage and fermentation process were studied. Results show a significant disintegration effect on WAS under optimal pretreatment conditions, with the peak concentration of SCOD, soluble protein, and soluble polysaccharide being 2059.5, 114.86, and 190.97 mg/L, respectively, which means that large amounts of intracellular carbon sources were released. The production of VFAs included acetic acid, propionic acid, isobutyric acid, n ‐butyric acid, isovaleric acid, and n ‐valeric acid, with a peak concentration of 9555.89, 1779.12, 608.84, 805.7, 777.91, 184.86 mg·COD/L, respectively. The content of PO4 3 ‐P and NH4 + ‐N were great in fermentation liquid, 71.82 and 320.75 mg/L, respectively. These results indicate that the synergistic process improve VFAs production and contribute to nutrients reuse.